Strengthening City Branding through Smart Economy Based on Local Economic Potential in Belitung Regency: JEL Classification: R11, R58, O18, O33, M31, L26, Z32 - Dessy Mayasari; I Gede Wyana Lokantara (Journal of Management and Administration Provision, 2026)
Belitung Regency possesses considerable local economic potential, supported by tourism, micro, small, and medium enterprises (MSMEs), the creative economy, and the fisheries sector. However, these potentials have not been fully realized as part of a strong regional identity in city branding. This study aims to analyze the role of the smart economy in strengthening city branding based on local economic potential in Belitung Regency. A descriptive quantitative approach was employed using a survey of 50 respondents, comprising MSME actors, creative economy practitioners, and tourism business operators. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, indicator ranking, and SWOT analysis. The results indicate that the implementation of the Smart Economy is at a moderate level, with an average score of 3.47. Innovative spirit (3.85), entrepreneurship (3.72), and economic opportunity (3.51) emerged as the dominant factors supporting local economic development. Meanwhile, city branding also remains at a moderate level, with an average score of 3.28, and is still largely characterized by a tourism-oriented image. Local economic potential, such as MSMEs, the creative economy, traditional culinary products, and fisheries products, has not yet developed into a primary representation of regional identity. The findings reveal that the smart economy does not directly lead to strong city branding. Its contribution depends on the region’s ability to integrate innovation, digital transformation, and local flagship products into a consistent territorial identity. This study highlights the importance of an economic branding approach to strengthen the identity and competitiveness of Belitung Regency sustainably.